Pelatihan Meningkatkan Kompetensi Penyelesaian Data Transaksi Perusahaan Dagang bagi Guru SMK di Jakarta Barat - Dizar, Shafrani; Murtanto; Yudhaputri, Egabetha Amirah; Zulkarnaen, Regita; Mir’az, Raffa Tianisyah; Nata, Sofian (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Education considered as a basic element in efforts to achieve national prosperity. In education, teachers have a role as an educator who’s responsible to teach values, ethics, morals and social aspects to students. With this responsibility, a teacher must have sufficient knowledge and understanding which will be conveyed to the students. Therefore, improving the quality and competence of teachers in Indonesia is an unavoidable necessity. There are some of vocational school teachers majoring in accounting who do not have adequate competence in accounting field, even though they teach this subject. Because of that issue so this Community Service activity is provided understanding and skills in trading company financial reporting. After counseling and training is carried out, hoped that vocational school teachers in West Jakarta can record trading company transactions and produce financial reports that comply with applicable accounting standards, and understand so they can carry out their duties. The training and counseling method is a training method on increasing competency in completing trading company transaction data. The training results showed that 16 of the 20 participants passed the competency test.